2022
DOI: 10.1155/2022/7715398
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Resources Optimal Operation Model of Multireservoir: A Case Study of Kuitun River Basin in Northwestern China

Abstract: Aiming at the problems that need to be solved urgently in the current operation of a multireservoir in Kuitun River Basin, such as the uneven distribution of water resources in time and space, the large workload of manual operation calculation, and low coordination level, the paper takes the optimal operation of water resources in the basin as the main goal and carries out the research on the optimal operation model of the multireservoir in combination with the complex characteristics of local water resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…This complexity underscores the importance of considering both atmospheric precipitation and the influence of temperature variation on the basin's upstream water source. The relevance of this approach is supported by similar studies in the Kuitun River Basin, where a significant correlation between runoff and precipitation was observed, aligning with the findings of the present study [41]. In contrast, Shang et al [20] reported that the relationship of runoff with the change in temperature is more complicated.…”
Section: Temporal Dynamics Of Seasonal Runoff Variationssupporting
confidence: 91%
“…This complexity underscores the importance of considering both atmospheric precipitation and the influence of temperature variation on the basin's upstream water source. The relevance of this approach is supported by similar studies in the Kuitun River Basin, where a significant correlation between runoff and precipitation was observed, aligning with the findings of the present study [41]. In contrast, Shang et al [20] reported that the relationship of runoff with the change in temperature is more complicated.…”
Section: Temporal Dynamics Of Seasonal Runoff Variationssupporting
confidence: 91%